The Effect of Highly Hydroxylated Fullerenol C60(OH)36 on Human Erythrocyte Membrane Organization - Jacek Grebowski; Anita Krokosz (Journal of Spectroscopy)
The mechanism of the interaction of highly hydroxylated fullerenol C60(OH)36 with erythrocyte membranes was studied by electron spin resonance spectroscopy (ESR) of stearic acid derivatives labeled with a nitroxyl radical at C-12 or C-16 and with a nitroxyl derivative of maleimide covalently attached to sulfhydryl groups of membrane proteins. A significant increase in membrane fluidity in the hydrophobic region of the lipid bilayer was observed for 12-doxylstearic acid at fullerenol concentrations of 100 mg/L or 150 mg/L, while for 16-doxylstearic acid significant increase in fluidity was only observed at 150 mg/L. Fullerenol at 100 mg/L or 150 mg/L caused conformational changes in membrane proteins, expressed as an increase in the hw/hs parameter, when fullerenol was added before the maleimide spin label (MSL) to the membrane suspension. The increase of the hw/hs parameter may be caused by changes in lipid-protein or protein-protein interactions which increase the mobility of the MSL label and as a result increase the membrane fluidity. Incubation of the membranes with the MSL before the addition of fullerenol blocked the available membrane protein –SH groups and minimized the interaction of fullerenol with them. This confirms that fullerenol interacts with erythrocyte membrane proteins via available protein –SH groups.